EDUKASI HIGIENE SANITASI PENJAMAH DEPOT AIR MINUM ISI ULANG DI KOTA PARIAMAN - Azyyati Ridha Alfian; Fea Firdani; Putri Nilam Sari (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
Water is a vital need in daily life. The need for drinking water for the community varies greatly. Pariaman City is one of the highest cities that use drinking water sources from Refill Drinking Water Depots (DAMIU), which is 56.1%. Based on laboratory tests on the quality of drinking water from DAMIU in Kota Pariaman, it shows that every year more than 50% of drinking water from DAMIU does not meet the health requirements and requirements for drinking water. This also occurs due to the low sanitation of drinking water depots. This activity aims to increase the knowledge of DAMIU owners or operators regarding sanitation hygiene. This activity was carried out in 30 DAMIU in Pariaman City. The method of activity is in the form of lectures, education, and giving posters for each DAMIU subject. Activity participants are DAMIU owners or operators who are on duty when the activity takes place. The increase in the knowledge of the target group was assessed using the pre-test and post-test methods regarding drinking water sanitation hygiene. Based on the results of activities based on the results of the pretest and post-test that have been carried out, there is an increase in the knowledge of DAMIU owners and operators regarding hygienic sanitation for drinking water, from 43.3% to 66.7%. From this activity, there was an increase in the target group's knowledge about hygiene and sanitation in this activity. It is hoped that the increase in knowledge of DAMIU owners and operators is followed by an increase in the quality of refill drinking water according to the required health standards.